(untitled) (Research, Society and Development, 2021)
The aims to understand the repercussions of the COVID-19 pandemic on the lives of undergraduate health students. It’s a qualitative study, of the participant action type, based on Paulo Freire’s theoretical methodological assumptions. Freire’s Research Itinerary was visited, which has three interconnected stages: Thematic Research; Encoding and Decoding; and Critical Unveiling. A virtual Culture Circle was held with the participation of 15 students from different universities in Santa Catarina, Brazil, in July 2020. The students highlighted that in the face of the pandemic they developed feelings of uncertainty, imminence of death, insecurity, anguish, discouragement, frustration, discomfort, anxiety, anger, concerns, fear, impotence and several doubts about the quality of their training. They pointed out that during the pandemic, it is necessary to reshape personal and academic priorities by means of moments that promote self-reflection, self-knowledge, empathy, love, resilience and protagonism. The investigation provided knowledge of the feelings that permeate the imagination of students of undergraduate health courses and unveil the transformations imposed by the pandemic, expanding the understanding related to the resignifications and ways of life found by them. The Virtual Culture Circle was interpreted as a therapeutic device and a research resource suitable for use in contexts where social distance is imperative.